2018
DOI: 10.3390/jcm7050115
|View full text |Cite
|
Sign up to set email alerts
|

Individualised Multimodal Treatment Strategies for Anaplastic and Poorly Differentiated Thyroid Cancer

Abstract: The prognosis of anaplastic (ATC) and poorly differentiated thyroid cancer (PDTC) is poor, due to their radioiodine refractoriness (RAI-R), high metastatic potential and current lack of effective treatment strategies. We aimed to examine the efficacy of the tyrosine kinase inhibitors (TKIs) sorafenib and selumetinib and the histone deacetylase inhibitor (HDACI) panobinostat in patient-derived tumor tissue (PDTT) of ATCs/PDTCs, the expression of sodium iodide symporter (NIS) and radioiodine up-take (RAI-U). Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…After behavioral analyses, the mice were anesthetized via a combination of ketamine and xylazine and euthanized, as previously described [6,38]. The brain parts were separated and homogenized in PRO-PREP TM extraction solution (iNtRON Biotechnology, Inc., Sungnam, South Korea) and centrifuged (13,000 RPM for 25 min at 4 • C).…”
Section: Immunoblotingmentioning
confidence: 99%
“…After behavioral analyses, the mice were anesthetized via a combination of ketamine and xylazine and euthanized, as previously described [6,38]. The brain parts were separated and homogenized in PRO-PREP TM extraction solution (iNtRON Biotechnology, Inc., Sungnam, South Korea) and centrifuged (13,000 RPM for 25 min at 4 • C).…”
Section: Immunoblotingmentioning
confidence: 99%
“…Poorly differentiated thyroid cancer (PDTC) remains one of the most aggressive cancers of the head and neck with a poor prognosis due to its radioiodine refractoriness, high metastatic potential and current limited armamentarium of effective treatment strategies. 1,2 The Walczyk retrospective study of 46 patients with PDTC Outcomes of this study showed that integration of AJCC stage, ATA risk and age group identifies six subgroups of patients with progressively worse DSS as AJCC stage, ATA risk and age increases, and in addition provides a more individualized estimate of DSS, especially in ATA high-risk patients. 4 From a histopathogenetic and clinical perspective, PDTCs are distinctive, and they have a risk of mortality, recurrence and metastasis that resides between that of well-differentiated thyroid cancers and anaplastic carcinomas.…”
mentioning
confidence: 96%
“…Poorly differentiated thyroid cancer (PDTC) remains one of the most aggressive cancers of the head and neck with a poor prognosis due to its radioiodine refractoriness, high metastatic potential and current limited armamentarium of effective treatment strategies …”
mentioning
confidence: 99%
See 2 more Smart Citations